Construction of porous hierarchical NiCo2S4 toward high rate performance supercapacitor - Zhao, Fenglin; Huang, Wanxia; Sial, Muhammad Aurang Z. G.; Xie, Dong; Wu, Hongliang; Zhang, Qi; Zou, Jizhao; Zeng, Xierong (Springer, 2019)
Developing high-performance supercapacitors is an effective way to satisfy the ever-increasing energy storage demand for emerging devices, but the inferior rate performance of battery-type supercapacitors limits their large-scale utilization. Herein, porous hierarchical nickel cobalt sulfide (NiCo2S4) was constructed by a novel strategy that the synthesized nickel cobalt oxide nanosheets as chemical template for hydrothermal method. Furthermore, the backbone of nickel cobalt oxide nanosheets can finally convert to NiCo2S4, which both plays the role of matrix to buffer the volume variation and enhances entire conductivity. Benefiting from high specific area (79.9 m2 g−1), suitable nanopores for KOH electrolyte, high conductivity, and multiple Co/Ni valence, the hierarchical NiCo2S4 electrode delivers a high specific capacity of 1035.1 F g−1 at the current density of 1 A g−1, and an ultrahigh rate performance of 80.9% capacitance retention at 20 A g−1 was obtained. The assembled asymmetric supercapacitor device could achieve the maximum capacity of 102.4 F g−1 at 5 mV s−1 and maintain at 80.5 F g−1 at 50 mV s−1, indicating its superior rate ability. In addition, the highest energy density of 35.4 Wh kg−1 can be obtained at a power density of 0.4 kW kg−1. These results indicate that the porous hierarchical NiCo2S4 could be served as high rate performance electrode materials for advanced supercapacitors.
Keywords: hierarchical structure; NiCo2S4; high specific area; supercapacitors